Paranoid Pedagogies Education, Culture, and Paranoia (Palgrave Studies in Educational Futures, 2018)
This edited book explores the under-analyzed significance and function of paranoia as a psychological habitus of the contemporary educational and social moment. The editors and contributors argue that the desire for epistemological truth beyond uncertainty characteristic of paranoia continues to profoundly shape the aesthetic texture and imaginaries of educational thought and practice. Attending to the psychoanalytic, post-psychoanalytic, and critical significance of paranoia as a mode of engaging with the world, this book further inquires into the ways in which paranoia functions to shape the social order and the material desire of subjects operating within it. Furthermore, the book aims to understand how the paranoiac imaginary endemic to contemporary educational thought manifests itself throughout the social field and what issues it makes manifest for teachers, teacher educators, and academics working toward social transformation. .